European nihilism and annihilation in the twentieth century - Elbe, Stefan (Totalitarian movements and political religions, 2000)
This article draws attention to Friedrich Nietzsche's discussion of the advent of European nihilism, or meaninglessness, as a way of illuminating our understanding of the violent and authoritarian politics of twentieth‐century Europe. In this vein, the article sets out by reviewing Nietzsche's analysis of European nihilism and suggests it was often the desire to escape this disconcerting experience that served to fuel the rise of authoritarian movements, as well as the violent conflicts that erupted between them. Subsequently, the article surveys some of the references, both scholarly and those based on lived experiences, which testify to the respective role played by the experience of meaninglessness in the two world wars, as well as the Cold War. The article concludes with a brief consideration of Nietzsche's own proposed strategy for confronting the advent of European nihilism.